1987
DOI: 10.2134/agronj1987.00021962007900040025x
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod Influence on Development in Sunflower Genotypes1

Abstract: Synchronization of anthesis of male and female inbred sunflower (Helianthus annuus L.) lines to be crossed in either breeding nurseries or seed production fields is important. Research was conducted to determine the influence of photoperiod on phenological development in a diverse group of sunflower genotypes. An understanding of this response would allow the development of a model to predict sunflower anthesis. Sixteen sunflower genotypes, including hybrid and inbred lines, were classified for photoperiod res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 10 publications
5
16
0
Order By: Relevance
“…However, their relative responses for time to flowering showed a strong hybrid group × subregion crossover interaction; the striped‐seed hybrids (group 1) showing intermediate‐early, intermediate‐late, and late maturities in the northern, central, and southern subregions, respectively. These relative responses for time to flowering are consistent with the findings of Goyne and Schneiter (1987) and Leon et al (2001) for the sunflower inbred lines ZENB8 and HA 89, female parents of some hybrids representative of group 1 and 2, respectively. According to these authors, HA 89, as well as other lines representative of group 2 like HA 300 (Goyne and Schneiter, 1987), exhibit an ambiphotoperiodic response (short‐ or long‐day response depending on photoperiod); it shows its longest relative maturity when the photoperiod at emergence is about 11 to 13 h and a long‐day response at longer daylengths.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, their relative responses for time to flowering showed a strong hybrid group × subregion crossover interaction; the striped‐seed hybrids (group 1) showing intermediate‐early, intermediate‐late, and late maturities in the northern, central, and southern subregions, respectively. These relative responses for time to flowering are consistent with the findings of Goyne and Schneiter (1987) and Leon et al (2001) for the sunflower inbred lines ZENB8 and HA 89, female parents of some hybrids representative of group 1 and 2, respectively. According to these authors, HA 89, as well as other lines representative of group 2 like HA 300 (Goyne and Schneiter, 1987), exhibit an ambiphotoperiodic response (short‐ or long‐day response depending on photoperiod); it shows its longest relative maturity when the photoperiod at emergence is about 11 to 13 h and a long‐day response at longer daylengths.…”
Section: Discussionsupporting
confidence: 87%
“…These relative responses for time to flowering are consistent with the findings of Goyne and Schneiter (1987) and Leon et al (2001) for the sunflower inbred lines ZENB8 and HA 89, female parents of some hybrids representative of group 1 and 2, respectively. According to these authors, HA 89, as well as other lines representative of group 2 like HA 300 (Goyne and Schneiter, 1987), exhibit an ambiphotoperiodic response (short‐ or long‐day response depending on photoperiod); it shows its longest relative maturity when the photoperiod at emergence is about 11 to 13 h and a long‐day response at longer daylengths. Relative to ZENB8, these HA 89 line types require more growing degree days to flower when the photoperiod during emergence is equal to or less than 14 h. This type of response reflects that of group 2 hybrids, which are relatively late in the northern subregion, where emergence and vegetative period occur under short photoperiods, and relatively early in the central and southern subregions, where later plantings and higher latitudes are associated with longer photoperiods for the same crop phase.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, Texan populations, known to have established during a relatively recent southward range expansion (Rieseberg et al, 1990; Whitney et al, 2006), exhibit a facultative long‐day response. Similar variation in photoperiod response is also observed among cultivated accessions, and cultivars with additional, more complex responses have been reported as well (Allard and Garner, 1940; Dyer et al, 1959; Goyne and Schneiter, 1987; Leon et al, 2001; Yanez et al, 2005; Blackman et al, 2010). However, with the exception of the Jerusalem artichoke, H. tuberosus , another taxon of agronomic interest in the genus (Hackbarth, 1937; Kays and Nottingham, 2008), the diversity of photoperiod response within and between Helianthus species has not been extensively surveyed.…”
supporting
confidence: 76%
“…comm.) although it has been reported that both short and long days can accelerate sunflower development (Doyle 1975, Hammer et al 1982, Goyne & Schneiter 1987. Flowering can occur over a wide range of daylengths and, hence, photoperiod was assumed to be inconsequential when predicting development over a wide range of locations (Kiniry et al 1992).…”
Section: Phenological Developmentmentioning
confidence: 99%